Decolonizing Time Work, Leisure, and Freedom - Shippen, Nichole Marie; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2014)
Decolonizing Time: Work, Leisure, and Freedom demonstrates the importance of time as a central category for political theory, providing not only a history of the fight for time through political, feminist, and critical theory, but also assessing this tradition in the context of the United States.
Keywords: Science; Science; Science, general